2006
DOI: 10.1088/0957-4484/17/12/038
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of particle shape on the phase stability of ZrO2nanoparticles

Abstract: At the nanoscale, zirconium dioxide may form in a number of different polymorphs, depending in part upon the size of the particles. Although considerable attention has been given to finding methods for controlling the phase of zirconium dioxide nanocrystals, the role of nanomorphology in affecting the size-dependent phase transition has been largely ignored. To address this issue, we have used a shape-dependent thermodynamic model to investigate the relationship between nanomorphology and phase stability. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 43 publications
4
44
0
1
Order By: Relevance
“…3.3) is only applicable to spherical particles, the approach was tested successfully in simulations for Si, Ge, nanodiamonds, and TiO 2 polymorphs. The authors predicted faceted shapes (e.g., cubes or tetrakaidecahedrons) as preferred shapes in very small sizes for most cases, which is contradictory to common sense (i.e., spheres) [9,83,85].…”
Section: Deviations Of the Models: The Determination Of Gmentioning
confidence: 99%
“…3.3) is only applicable to spherical particles, the approach was tested successfully in simulations for Si, Ge, nanodiamonds, and TiO 2 polymorphs. The authors predicted faceted shapes (e.g., cubes or tetrakaidecahedrons) as preferred shapes in very small sizes for most cases, which is contradictory to common sense (i.e., spheres) [9,83,85].…”
Section: Deviations Of the Models: The Determination Of Gmentioning
confidence: 99%
“…The most stable forms calculated for zirconia nanoparticles have habit changes at 8 and 12.7 nm diameters (Barnard et al 2006). …”
Section: Size Mattersmentioning
confidence: 99%
“…Therefore, crystal modeling has become a fundamental tool because of its use in the prediction of crystal shapes, growth processes, and the resulting properties of an unlimited number of systems. [2][3][4][5] A major issue in crystal modeling is to describe how synthesis parameters and the chemical environment influence the nanocrystal morphology and surface-energy distribution. Some studies have reported that the surface-energy distribution is dependent on the local composition in doped systems.…”
Section: Introductionmentioning
confidence: 99%